A theory of art : inexhaustibility by contrast - Ross, Stephen David (SUNY series in systematic philosophy., 1982)
Art is among the most typical, pervasive, and fundamental of human activities, taking a remarkable variety of forms and imbued with an apparently unquenchable drive toward novelty and variation. Given its pervasiveness throughout human life, we may wonder why we have so little understanding of the nature of art. We lack even a rudimentary understanding of art in general -- though we possess remarkable insights into individual works and periods. Yet given the variety of works, styles, an darts, it is not surprising that we have no adequate general theory of art, for every such theory is dissipated into new forms and developments in artistic production. It is [the] intention with this book to provide a general understanding of the richness and power of works of art, in their myriad forms, including masterpieces but also lesser known achievements, including acknowledged failures. -- From preface.